Regulatory and Mechanistic Actions of Glucocorticoids on T and Inflammatory Cells - Liberman, Ana C.; Budziñski, Maia L.; Sokn, Clara; Gobbini, Romina Paula; Steininger, Anja; Arzt, Eduardo (Frontiers in Endocrinology, 2018)
Glucocorticoids (GCs) play an important role in regulating the inflammatory and immune response and have been used since decades to treat various inflammatory and autoimmune disorders. Fine-tuning the glucocorticoid receptor (GR) activity is instrumental in the search for novel therapeutic strategies aimed to reduce pathological signaling and restoring homeostasis. Despite the primary anti-inflammatory actions of GCs, there are studies suggesting that under certain conditions GCs may also exert pro-inflammatory responses. For these reasons the understanding on the GR basic mechanisms of action on different immune cells in the periphery (e.g. macrophages, dendritic cells, neutrophils and T cells) and and in the brain (microglia) contexts, that we review in this chapter, is a continuous matter of interest and may reveal novel therapeutic targets for the treatment of immune and inflammatory response.